2017
DOI: 10.1002/1878-0261.12070
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of everolimus and 5‐aza‐2′‐deoxycytidine in medullary thyroid carcinoma cell lines

Abstract: Medullary thyroid cancer (MTC) is a tumor highly resistant to chemo‐ and radiotherapy. Drug resistance can be induced by epigenetic changes such as aberrant DNA methylation. To overcome drug resistance, we explored a promising approach based on the use of 5‐aza‐2′‐deoxycytidine (AZA), a demethylating agent, in combination with the mTOR inhibitor everolimus in MTC cells (MZ‐CRC‐1 and TT). This combined treatment showed a strong synergistic antiproliferative activity through the induction of apoptosis. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Among these, the neurotrophin signaling pathway was most directly involved in apoptosis, through NGFR and Bax gene overexpression. Increased expression of genes involved in the NGFR-MAPK10-TP53-Bax/Bcl2 pathway during incubation with AZA plus everolimus was validated by western blotting in MZ-CRC-1 cells [84].…”
Section: Sprouty1 (Spry1)mentioning
confidence: 90%
“…Among these, the neurotrophin signaling pathway was most directly involved in apoptosis, through NGFR and Bax gene overexpression. Increased expression of genes involved in the NGFR-MAPK10-TP53-Bax/Bcl2 pathway during incubation with AZA plus everolimus was validated by western blotting in MZ-CRC-1 cells [84].…”
Section: Sprouty1 (Spry1)mentioning
confidence: 90%
“…For instance, a study found that the inhibition of CCDC69 was hypermethylated in ovarian cancer cells and might interfere with the effectiveness of combination therapy with platinum drugs, which means the combination of 5‐Aza‐dC and other anti‐cancer drugs may have better effect . To overcome drug resistance, some researchers explored a promising approach using 5‐Aza‐dC and the mTOR inhibitor everolimus in Medullary thyroid cancer cells, which showed a strong synergistic antiproliferative activity through the induction of apoptosis . Certainly, the studies of co‐treatment in renal cancer are not rare.…”
Section: Discussionmentioning
confidence: 99%
“…31 To overcome drug resistance, some researchers explored a promising approach using 5-Aza-dC and the mTOR inhibitor everolimus in Medullary thyroid cancer cells, which showed a strong synergistic antiproliferative activity through the induction of apoptosis. 32 Certainly, the studies of co-treatment in renal cancer are not rare.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the results from the Venn diagram, all genes were included in RRA result. These iDEGs were predominantly enriched in the pathways 'PI3K-Akt signaling pathway', 'focal adhesion', 'ECM-receptor interaction' and the 'calcium signaling pathway' (24)(25)(26). A total of 7 hub genes were identified from the PPI network, which was composed of 493 iDEGs.…”
Section: Discussionmentioning
confidence: 99%